(untitled) (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2023)
This paper deals with the investigation of Qatari women’s short story at the end of the 20th – the beginning of the 21st centuries. The author determines the contribution of women’s literary output in the development of the short story genre in Qatari literature. In the late ‘70s and ‘80s, Qatari short story had a great development due to the works of such writers as Kaltham Jabr, Umm Aktham, Nura Al Saad, Ḥeṣṣa al-Jabir and Mayisa al-Khalifi. In their works, they began to depict the inner world of the characters and abandoned the direct representation of reality. As a result, they modernized the form of a short story. The short story collections "The Pain of an Arab Woman" ("وجع امرأة عربية", 1993 р.) by Kaltham Jabr and "Newspaper Seller" ("بائع الجرائد", 1989 р.) by Nura Al Saad attracted great attention of Arab critics with their novelty. In their opinion, they became a leap in the development of Qatari short story. Among the representatives of the generation of the 1990s and 2000s, the short story collections of Huda al-Naimi, Nurah Faraj, and Dalal Khalifah stand out. The themes and stylistic features of their short stories have been briefly outlined. Dalal Khalifa’s short story collection "I am a Flower of White Jasmine" ("أنا الياسمينة البيضاء", 2002 р.) was chosen for a more detailed analysis, taking into consideration the significant contribution of Dalal Khalifah to the development of prose genres in Qatari literature. In short stories from this collection Dalal Khalifah reveals the inner conflicts of the individual due to the skillful use of modernist narrative techniques.